Adsorpsi Logam Berat Menggunakan Selulosa Xanthat dari Bagas Tebu - Iryani, Dewi Agustina; Risthy, Nisa Meutia; Br. Ginting, Simparmin; Darmansyah, Darmansyah (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2019)
The most effective way to reduce the pollution of heavy metal waste is the adsorption process using an adsorbent. Sugarcane bagasse is one of materials that has high affinity to absorb heavy metals. The adsorption capacity of sugarcane bagasse can be increased by converting it into cellulose xanthate by reaction of cellulose with carbon disulfide (CS2). Synthesis of cellulose xanthate consists of three stages, i.e isolation, alkalization, and xanthation. In this study, the preparation of cellulose xhantate was conducted by adding carbon disulfide (CS2) about 180% (w/w). The temperature of xhantation reaction was varied at 35C, 40C and 45C. The effect of temperature reaction into degree of substitution (DS), the degree of polymerization (DP) and the metal adsorption capacity of cellulose xanthate for Zn2+ and Pb2+ were determined by quantitative and qualitative analyze. Morphological characteristics of cellulose xanthate was characterized by SEM and the functional groups contained in the cellulose xanthate was characterized by FTIR. The result showed that cellulose xanthate synthesized at temperature of 35C have a highest value of DS, DP, and the adsorption capacity higher than two variations of temperature (40C and 45C). The value of DS, DP, and the adsorption capacity is 0.389, 299.27, 48.353 mg/g for Zn2+ metal and 51.763 mg/g for the metals Pb2+, respectively